PENGARUH CAR, NPF, DAN BOPO TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH DI INDONESIA TAHUN 2015-2019 - Adhalia Pratiwi; Nana Diana (Universitas Muhammadiyah Jember, 2021)
This research aimed to know and analyze the influence of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), and Operational Efficiency (BOPO) against profitability (ROA) of Islamic commercial bank in Indonesia from 2015-2019 . The data used in this study are secondary data taken from the annual financial statements of Islamic commercial bank in Indonesia. Research Method using quantitative method with purposive sampling method. The analysis method used in this research is Multiple Linear Regression Test. The sample of this research is 12 Islamic commercial bank in 5 years from 14 population. The results of this research indicate that no partial effect of CAR on ROA but NPF and BOP has a partial effect on ROA. While simultaneously the CAR, NPF and BOPO variabels have an effect on ROA